A Gathering of Medieval English Recipes - Hieatt, Constance B. (Brepols, 2008)
This book is a collection of medieval English culinary recipes which have not been edited before. Some of them come from brief collections which have not been previously published, or are found in isolation or very small groups in manuscripts which do not contain such collections. Others come from collections which have been used, or viewed, primarily for collation, but which contain other recipes which had not yet been noted. It was the author's object to gather together all the recipes which had not been edited and published, or are not currently being edited by others, to make the record of English recipes of this period as complete as possible. The volume concludes with a supplement to the recently published <span class=